2018
DOI: 10.1093/jrr/rry073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metallic tools on scattered radiation dose during the use of C-arm fluoroscopy in orthopaedic surgery

Abstract: This study investigated the effect of metallic tools on the scattered radiation dose delivered to surgeons' radiosensitive organs while simulating hip surgery using C-arm fluoroscopy. Two phantoms, a pelvis and a Rando phantom, were used to simulate a patient and a surgeon in this study. Photoluminescence dosimeters were inserted into the Rando phantom in the positions of the eye, thyroid and gonad. A drill was positioned above the hip of the pelvis phantom or beside the pelvis phantom of the same height. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…23 Mini C-arm imaging provides temporal, anatomical information and real-time imaging of skeletal structures with the ability to confirm bony alignment and positioning as well as accurate placement of implants. 19,25,27 While the mini C-arm has many benefits, it is an additional piece of equipment in the OR with the potential for intraoperative contamination and, theoretically, surgical site infection (SSI). 7,24,26…”
Section: Introductionmentioning
confidence: 99%
“…23 Mini C-arm imaging provides temporal, anatomical information and real-time imaging of skeletal structures with the ability to confirm bony alignment and positioning as well as accurate placement of implants. 19,25,27 While the mini C-arm has many benefits, it is an additional piece of equipment in the OR with the potential for intraoperative contamination and, theoretically, surgical site infection (SSI). 7,24,26…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (5)(6)(7) have shown that radiation exposure can be reduced through protection methods in the following 3 categories: personal protective equipment (PPE) used by individuals, proper operation of C-arm fluoroscopy, and protection devices attached to the operating table or x-ray tube. Although it would be ideal to use these protective devices simultaneously, most hospitals do not have all these protective devices in actual clinical settings.…”
mentioning
confidence: 99%